DRY EYE (SHUSHKAKSHIPAKA) AND MENOPAUSE – A SURVEY STUDY (AYUSHDHARA, 2018)
Dry eye occurs when there is inadequate tear volume or function resulting in an unstable tear film and ocular surface disease. It is extremely common condition, particularly in postmenopausal women and the elderly. Although epidemiological studies investigating the prevalence of dry eye disease are rare, published studies indicate that up to 20% of adults aged 45 years or more experience dry eye symptoms. Menopause is permanent cessation of menstruation at the end of reproductive life which is the natural biological process. During this period there is gradual progressive loss of ovarian follicular activity. The increase incidence of dry eye in males than in females shows a positive impact stating there is hormonal impact on the disease. Androgens are the prime hormones responsible for regulation of lipid production. Oestrogen and progesterone receptors in the conjunctiva and lacrimal glands are essential for the normal function of these tissues. In Ayurveda, the disease comes under Sarvagata Roga and is named as Shushkakshipaka where in there will be depletion of Ashru leading to Shushka netra, which afflicts whole eye in the later stages. In menopausal women there will be Rasakshaya leading to Vata vriddhi. This impairs the normal functioning of the Netra where in the Shushkata will increase leading to many other symptomatology. To elucidate the relationship between menopause and dry eye, a survey study has been conducted in OPD and IPD of Sri Kalabyraweshwaraswamy Ayurvedic medical college, hospital and research centre, Bangalore which is affirmed.